'First, Do No Harm'... A Call to Re-evaluate the Wellbeing of Healthcare Staff - Kyriaki-Barbara Papalois (University Library System, University of Pittsburgh, 2023)
'Primum non nocere' or 'do no harm' is the timeless Hippocratic mantra instilled in every healthcare professional at the beginning of their career.  It is the ethical compass which guides all decision making in healthcare working in the best interests of patients to give them the best possible treatment and quality of life. This vocation of course does not  come without its  challenges, long working hours, stress, time constraints  and demands which affect the professional and personal life of healthcare workers and in some instances their own health and wellbeing. It is time to raise the profile of this truth and call for ways to practically encourage health professionals to make  their well being  a priority too.